The Significance of Eosinophil-to-Lymphocyte Ratio in Predicting Response to Omalizumab Treatment in Patients with Bullous Pemphigoid: A Case Series - Gülfem Akin; Ceylan Avci; Sevgi Akarsu (Indian Journal of Dermatology)
Omalizumab, a monoclonal anti-IgE antibody, has been used off-label in a few case series of bullous pemphigoids (BPs) with rapid efficacy and high safety profile. However, there is a lack of data to select patients who would get the most therapeutic benefit from omalizumab therapy. To assess if eosinophil-to-lymphocyte ratio (ELR), total serum IgE level, and serum eosinophil percentage would be useful in predicting response to omalizumab therapy in patients with BP. Medical records of 10 patients with BP treated with omalizumab were retrospectively analysed for clinical and laboratory data. ELRs, total serum IgE levels, and serum eosinophil percentages were compared between groups of complete responders and partial responders/flare-ups, but the results were not statistically significant. Studies with larger sample sizes should be done to predict the role of type 2 immunity markers in omalizumab therapy of BP patients.